Collaboration: chronological boundaries - Kasperavičius, Algis (Genocidas ir rezistencija, 2001)
Unlike such terms as ‘resistance’, ‘occupation’, ‘annexation’, and ‘genocide’, which are also bound to be disputed, the term ‘collaboration’ is the least scientific term, and the least legal one. Like many terms, it can be used in the science of history and journalism, but it is always questionable, because different groups of people have different views of their relationship to the occupying authority.
Keywords: collaboration; Soviet occupation; communist party